2021
DOI: 10.1107/s2052520621006399
|View full text |Cite
|
Sign up to set email alerts
|

Properties and interactions – melting point of tribromobenzene isomers

Abstract: Single crystals of isomeric 1,2,3-tribromobenzene (123TBB), 1,2,4-tribromobenzene (124TBB) and 1,3,5-tribromobenzene (135TBB) have been grown from different solvents and their structures determined by X-ray diffraction at 100, 200 and 270 K. The melting-point differences of ca 40 K between 135TBB, 123TBB and 124TBB have been correlated with the molecular symmetry and packing preferences in the crystal, as well as with the main types of intermolecular halogen interactions, i.e. Br...Br, Br...C (Br...π) and Br..… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Equation 4 in Wei (1999), and its inversed version above, both involve the enthalpy loss ÁH, depending on the cohesion forces in the crystal. The calorimetric parameters of bromobenzene isomers C 6 H n Br 6-n (Bujak et al, 2021) are not as well and completely determined as those for chlorobenzenes C 6 H n Cl 6-n . Hence in our research we focused on the determination of their crystal structures, and in particular on comparing halogen bonds BrÁ Á ÁBr.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Equation 4 in Wei (1999), and its inversed version above, both involve the enthalpy loss ÁH, depending on the cohesion forces in the crystal. The calorimetric parameters of bromobenzene isomers C 6 H n Br 6-n (Bujak et al, 2021) are not as well and completely determined as those for chlorobenzenes C 6 H n Cl 6-n . Hence in our research we focused on the determination of their crystal structures, and in particular on comparing halogen bonds BrÁ Á ÁBr.…”
mentioning
confidence: 88%
“…Our recent paper (Bujak et al, 2021) reported the crystal structures of isomeric 1,2,3tribromobenzene, 1,2,4-tribromobenzene and 1,3,5-tribromobenzene determined by single-crystal X-ray diffraction as a function of temperature (at T = 100, 200 and 270 K). We analysed the intermolecular interactions as well as the crystal and molecular symmetry in relation to the melting point (T m ) of these compounds.…”
mentioning
confidence: 99%
“…12 Several crystal structures of halobenzenes have been reported and discussed in a series of papers by Bujak and co-workers. [13][14][15][16] In all of these studies, discussion of the crystal structures has focussed on approaches containing one, two or three favourable connections, sometimes denoted "synthons", including halogen⋯halogen and C-H⋯halogen connections.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, Bujak et al (2021) try to rationalize the melting points of three isomers of tribromobenzene using 'Carnelley's rule': in a set of isomers, the higher the molecular symmetry, the higher the melting point (Carnelley, 1882a,b). Indeed, 1,2,4-tribromobenzene melts at 317.7 K, whereas 1,3,5-tribromobenzene melts at 396.0 K. The authors try to use Carnelley's rule to argue that the higher the molecular symmetry, the more optimal the molecular interactions in the crystal structure and therefore the higher the melting point.…”
mentioning
confidence: 99%